Cultural challenges to faith: a reflection on the dynamics of modernity - O'Callaghan, Paul (Church, Communication and Culture, 2017)
The primary challenge modern culture offers Christian faith is that the former is itself the fruit of a historico-cultural process deeply influenced by Christian faith. In many ways modern culture is an elevated, sophisticated one, containing a great variety of precious anthropological insights and strengths, with a surprising adaptability and openness to absorb, to clarify and to unite. However in the present moment it comes across, in many cases, as a 'culture without faith', a culture wilfully disconnected from the faith that gave life to it in the first place, and thus, ultimately, a fragile culture. This has led many of those influenced by modern culture to a generalised loss of faith and to a pathology of individualism and ingratitude, as they attempt to live in isolation from their fellows, unprepared to recognise the world they live in and the privileges they enjoy as God's gifts. This suggests the need to widen the scope of human rationality in two directions: with others and towards others; other humans and ultimately God, the source of all goodness and truth. This study will consider the relationship between culture and Christian faith in terms of the influence of faith on culture and of culture on faith, with a view to understanding (1) how modern culture, formed and informed to an important degree by faith, now challenges faith anew to provide answers to questions that have not been asked before, and (2) how faith can challenge culture anew, not just by providing solutions but also by posing new questions. The topic of course is very ample and complex, and so the study will only provide an introductory reflection.